Differential Diagnosis between Anomalous Experiences and Dissociation Disorder Using the Dissociative Disorders Interview Schedule (DDIS). Issue 2 (15th March 2019) - Vencio, Sérgio; Caiado-Vencio, Rafael; Caixeta, Leonardo
ABSTRACT: Background . It is important to understand the most diverse cultural aspects related to religiosity. Scientifically, it is important to understand religious manifestations and their relation to health, and to differentiate them from psychopathological manifestations. Objective . To evaluate the mental health of a group of mediums and compare it with that of a control group from the same religious context who do not manifest mediumship, using the Dissociative Disorders Interview Schedule (DDIS). Methods . This was a cross-sectional study, evaluating 47 mediums (Group 1) and comparing them with 22 non-medium volunteers from the same religious context (Group 2) using the DDIS questionnaire. All results were matched with historical data from patients with dissociative identity disorder (DID) who answered the DDIS. Results . Scores obtained from the DDIS were similar in both groups. The number of positive symptoms was comparable in a wide range of analyzed areas, involving but not being restricted to somatization disorder, major depressive episode, borderline personality disorder, extrasensory/paranormal experiences, physical/sexual abuse and five dissociative disorders. There were considerable differences when we compared these results with historical data from patients with DID. Conclusion . In agreement with the extant literature, these results showed that mediumship can be considered a non-pathological form of dissociative phenomena.